Successful avatrombopag combined with cyclosporine treatment for carboplatin/pegylated liposomal doxorubicin/bevacizumab-induced acquired amegakaryocytic thrombocytopenia in a patient with recurrent ovarian cancer: case report - Meng, Weikang; Hua, Jinsheng; Wang, Jiabing (Frontiers in Oncology, 2024)
Carboplatin/pegylated liposomal doxorubicin/bevacizumab is an accepted standard anti-cancer treatment option for recurrent ovarian cancer. However, the occurrence of adverse events associated with this therapeutic regimen limits its continued clinical use. Among these adverse events, acquired amegakaryocytic thrombocytopenia is rare but often potentially life-threatening adverse effect, and intolerant to multiple treatment approaches. We reported for the first time the successful treatment of avatrombopag combined with cyclosporine in one case of carboplatin/pegylated liposomal doxorubicin/bevacizumab-induced acquired amegakaryocytic thrombocytopenia, which was refractory or intolerant to glucocorticoids, intravenous immunoglobulin, recombinant human thrombopoietin, androgen and even thrombopoietin receptor receptor agonist eltrombopag and herombopag. To date, this case manifested as normal platelet counts and are independent of transfusion. Our findings suggest that this combination is a potential and valuable alternative in acquired amegakaryocytic thrombocytopenia.